1
$\begingroup$

I think the title is quite self-explanatory. I'm only allowed to use the definition of a derivative to differentiate the above function. Sorry for the formatting though.


Let $f(x) = \frac{x}{x^2+1}$

$$ \begin{align} f'(x)&= \lim_{h\to 0} \frac {f(x+h)-f(x)}{h}\\ &= \lim_{h\to 0} \frac {\frac{x+h}{(x+h)^2+1}-\frac{x}{x^2+1}}{h}\\ &= \lim_{h\to 0} \frac{\frac{x+h}{x^2+2hx+h^2+1}-\frac{x}{x^2+1}}{h}\\ &= \lim_{h\to 0} \frac{\frac{(x+h)(x^2+1)-x(x^2+2hx+h^2+1)}{(x^2+1)(x^2+2hx+h^2+1)}}{h}\\ &= \lim_{h\to 0} \frac{\frac{hx^2-2hx-h^2+h}{(x^2+1)(x^2+2hx+h^2+1)}}{h} \end{align} $$


I'm currently stuck with simplify the fraction so that I can finally find the derivative. I'd really appreciate some advice on how to proceed with the problem.

$\endgroup$
  • 1
    $\begingroup$ You can factor an $h$ from the numerator. That cancels with the one in the denominator. $\endgroup$ – iamwhoiam Sep 12 '17 at 3:37
  • 1
    $\begingroup$ Note that you can factor out an h from the numerator and cancel out the h in the denominator. Then you can just evaluate the limit by plugging 0 in for h $\endgroup$ – themathandlanguagetutor Sep 12 '17 at 3:40
  • 1
    $\begingroup$ Alternatively, to see it better, first simplify the compound fraction. Recall $$\frac{\,\frac{a}{b}\,}{c}=\frac{a}{bc}$$ and then factor out $h$ from numerator and denominator. $\endgroup$ – quasi Sep 12 '17 at 3:41
  • 1
    $\begingroup$ I think you should double check the step between your last two lines though $\endgroup$ – themathandlanguagetutor Sep 12 '17 at 3:43
2
$\begingroup$

Your last step is wrong, the actual steps will be,

$$=\lim_{h\to 0} \frac{\frac{-\color{red}{(hx^2-h+h^2x)}}{(1+x^2)(x^2+2hx+h^2+1)}}{\color{red}{h}}$$ $$=\lim_{h\to 0} \frac{\frac{-\color{blue}{(x^2-1+hx)}}{(1+x^2)(x^2+2hx+h^2+1)}}{\color{blue}{1}}$$

$$=\frac{1-x^2}{(1+x^2)^2}$$

$\endgroup$
2
$\begingroup$

\begin{eqnarray} {1 \over h } ({x+h \over 1 + (x+h)^2} - {x \over 1+x^2}) &=& {1 \over h } { (x+h)(1+x^2) - (1+(x+h)^2)x\over (x+x^2) (1 + (x+h)^2} \\ &=& {1 \over h } { h -h x^2 - h^2 x\over (x+x^2) (1 + (x+h)^2} \\ &=& { 1 - x^2 - h x\over (x+x^2) (1 + (x+h)^2} \end{eqnarray} The limit follows by taking $ h \to 0$.

$\endgroup$
1
$\begingroup$

\begin{align} f'(x) &= \lim_{h\to 0} \frac {f(x+h)-f(x)}{h}\\ &= \lim_{h\to 0} \frac {\frac{x+h}{(x+h)^2+1}-\frac{x}{x^2+1}}{h}\\ &= \lim_{h\to 0} \frac{(x+h)(x^2+1)-x((x+h)^2+1)}{h(x^2+1)((x+h)^2+1)}\\ &= \lim_{h\to 0} \frac{h - h^2x - hx^2}{h(x^2+1)((x+h)^2+1)} \end{align}

$$= \lim_{h\to 0} \frac{1 - hx - x^2}{(x^2+1)((x+h)^2+1)}$$ $$=\frac{1 - x^2}{(x^2+1)^2}$$

There are two common ways to compute a derivative. This is the other.

\begin{align} \left. f'(x) \right|_{x=x_0} &= \lim_{x\to x_0} \frac {f(x)-f(x)} {x-x_0}\\ &= \lim_{x\to x_0} \frac {\frac{x}{x^2+1}-\frac{x_0}{x_0^2+1}} {x-x_0}\\ &= \lim_{x\to x_0} \frac {x(x_0^2+1)-x_0(x^2+1)} {(x^2+1)(x_0^2+1)(x-x_0)}\\ &= \lim_{x\to x_0} \frac {(x x_0^2 - x_0 x^2) + (x-x_0)} {(x^2+1)(x_0^2+1)(x-x_0)}\\ &= \lim_{x\to x_0} \frac {-x x_0(x-x_0) + (x-x_0)} {(x^2+1)(x_0^2+1)(x-x_0)}\\ &= \lim_{x\to x_0} \frac {-x x_0 + 1} {(x^2+1)(x_0^2+1)}\\ &= \frac{1-x_0^2} {1+(x_0^2)^2}\\ \end{align}

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.